If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -8x = 51 + -36x Solving 11 + -8x = 51 + -36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36x' to each side of the equation. 11 + -8x + 36x = 51 + -36x + 36x Combine like terms: -8x + 36x = 28x 11 + 28x = 51 + -36x + 36x Combine like terms: -36x + 36x = 0 11 + 28x = 51 + 0 11 + 28x = 51 Add '-11' to each side of the equation. 11 + -11 + 28x = 51 + -11 Combine like terms: 11 + -11 = 0 0 + 28x = 51 + -11 28x = 51 + -11 Combine like terms: 51 + -11 = 40 28x = 40 Divide each side by '28'. x = 1.428571429 Simplifying x = 1.428571429
| -144-7x=10x+22 | | 5x^3+2x^2+8x-10=0 | | 4v-5v=-4 | | 9a-4=41 | | 9a-4=4 | | 5x+1x=-3 | | 4(3x+2)-4= | | x^3-3x^2-7x+a=0 | | 3x=25-y | | 5=4x-9+x-3x | | X-4=0.5X | | 100=2x-x+4x | | 1/2(18-5x)=1/3(6-4x) | | 3x-5y=-18 | | x+15+3=25+10 | | 16d=8 | | 12x-17-9=4 | | 9x+5-(3x+3)=32 | | 2x*34x= | | 10b-13b+20b= | | 85-2x=97-3x | | 12=(30*x)/(30+x) | | 2x+12=4x-50 | | 12=30*x/(30+x) | | 12=30*x/30+x | | 12=30*x/30*x | | (x-5)+(x-3)+x+(x+5)=29 | | 2a-b+3a+4b= | | 42x+51-17x+23=182+13x | | 3x^2+6x=2 | | 3(x+4)=16 | | 11x-25=5x+59 |